การวัดและประเมินผลตอบแทนทางสังคมจากการลงทุนในการผลิตครุศาสตรดุษฎีบัณฑิต สาขาวิชาการวัดและประเมินผลการศึกษา จุฬาลงกรณ์มหาวิทยาลัย - ฑิตยา สิทธิโสภาสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This study aimed to: (1) investigate and develop impact mapping and indicators of Social Returns on Investment (SROI) for Doctor of Philosophy Program in Educational Measurement and Evaluation, (2) investigate and develop financial proxies for Doctor of Philosophy Program in Educational Measurement and Evaluation, (3) develop the tool used in the measurement and evaluation of SROI for Doctor of Philosophy Program in Educational Measurement and Evaluation, and (4) evaluate SROI for Doctor of Philosophy Program in Educational Measurement and Evaluation, Chulalongkorn University. Methods: Evaluation research with mixed methods design was conducted. Applying SROI principles, in-depth interview was conducted with the stakeholders in the production of Ph.D. graduates based on theory of change. Indicators of impact were developed, and the financial proxies – the qualitative values created by the program were assigned to the impact. These values were subsequently calculated to compare with a monetary value of resources invested in undertaking the program’s activities to assess the social returns achieved in every baht invested in the production of Ph.D. graduates. The Instruments used were comprised of interview questions and a questionnaire inquiring about SROI in Ph.D. education. SROI analysis was operated using mean, percentage, impact values, discount rate, sensitivity analysis, social return on investment ratio (until the retirement age at 60) for the Ph.D. graduates of Educational Measurement and Evaluation Program, Curriculums B.E. 2535; 2541; 2549; and 2551, Chulalongkorn University. The data in this study was collected from 102 Ph.D. graduates who completed the degree during 1995 to 2016. Findings: (1) Impact Mapping. It was found that the inputs, the invested resources in the production of Ph.D. graduates consisted of personal investment and social cost. The activities or procedures of the program were comprised of six components. The output, the results of the program activities were comprised of four components. The outcomes, the benefits/changes undergone by the stakeholders of the project were comprised of 16 components. The Impacts, the effects of the stakeholders on social; economic and environment or the social impacts of the program were comprised of 10 components. There were 27 indicators for SROI of Ph.D. graduate production from 10 dimensions of impacts. Means of accuracy, causality and usefulness were ranging from 0.52 to 0.92 shows that these indicators can be used to develop questionnaires. (2) Out of 27 indicators for SROI, 25 indicators could be used in developing the financial proxies. Means of accuracy, causality and usefulness were ranging from 0.52 to 0.84 shows that these financial proxies can be used to develop questionnaires. (3) The measurement and evaluation tool of SROI for the production of Ph.D. graduates was a questionnaire which consisted of four sections and included both open- and closed- ended questions. The questionnaire items were validated, the means were ranging from 0.52 to 0.92 and the reliability of the questionnaires in part 2 3 and 4 was 0.548  0.618 and 0.800 respectively show that the questionnaire has the appropriate quality. (4) The SROI was 23.04. In case of investment in the production of Ph.D. graduate in Measurement and Evaluation Program, Chulalongkorn University provided a social return of 15.72, entailing a return of 12.07 to their organizations and 3.65 to the government. Meanwhile, these graduates provided a private return of 7.31 to themselves and their families.